CENTRAL RED PHOSPHORITES ENRICHMENT METHODS. REVIEW. (Multidisciplinary Journal of Science and Technology, 2024)
This analytical article provides detailed information about the methods of beneficiation of Central Kyzylkum phosphorites and the effect of physico-chemical factors affecting its productivity. The properties of thermal beneficiation of phosphate ores and other beneficiation were studied. Also, some information about the advantages and disadvantages of this enrichment is given.